2014
DOI: 10.1515/ract-2014-2163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humic acid on plutonium sorption to gibbsite: Determination of Pu-humic acid complexation constants and ternary sorption studies

Abstract: In this work stability constants describing Pu(IV), Th(IV), and Np(V) binding to Leonardite humic acid (HA) were determined using a discrete pK model. A hybrid ultra-filtration/equilibrium dialysis, ligand exchange technique was used to generate the partitioning data. Ethylenediaminetetraacetic acid (EDTA) was used as a reference ligand to allow the aqueous chemistry of the Pu(IV)-HA system to be examined over a range of pH values, while minimizing the possibility of precipitation of Pu(IV). The conditional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
(75 reference statements)
4
19
0
Order By: Relevance
“…Similar decreases in Pu(IV) sorption were also observed in ternary experiments of HA-Pu(IV)-gibbsite at pH 6 34 . In our experiments, the presence of HA strongly affected the behavior of Pu resulting in increased aqueous Pu concentrations.…”
Section: Pu Sorption In the Presence Of Humic Acidsupporting
confidence: 79%
“…Similar decreases in Pu(IV) sorption were also observed in ternary experiments of HA-Pu(IV)-gibbsite at pH 6 34 . In our experiments, the presence of HA strongly affected the behavior of Pu resulting in increased aqueous Pu concentrations.…”
Section: Pu Sorption In the Presence Of Humic Acidsupporting
confidence: 79%
“…Several studies have shown that the fate of Pu in the environment may be controlled by transport on colloidal iron oxide and clay mineral particles. [16][17][18] Additional studies have demonstrated that association of Pu with organic colloids can enhance pore water concentrations [19][20][21][22][23][24][25][26][27] . Moreover, the presence of organic matter can affect the oxidation state as it is known that Pu is rapidly reduced from Pu(VI)/Pu(V) to Pu(IV)/Pu(III).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Th(IV) and Pu(IV) have been shown to complex similarly in the presence of humic substances. However, Zimmerman et al (2014) measured only slightly greater sorption for Th than Pu after 10 days in batch experiments with 10 mg C /L as humic acid. Further, complexation constants have been measured to be up to three orders of magnitude greater for Pu(IV) as compared to Th(IV) as measured in 0.1 M NaCl and 10 mg C /L of humic acid for pH 4-7 (Artinger et al, 2003;Zimmerman et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…However, Zimmerman et al (2014) measured only slightly greater sorption for Th than Pu after 10 days in batch experiments with 10 mg C /L as humic acid. Further, complexation constants have been measured to be up to three orders of magnitude greater for Pu(IV) as compared to Th(IV) as measured in 0.1 M NaCl and 10 mg C /L of humic acid for pH 4-7 (Artinger et al, 2003;Zimmerman et al, 2014). It is clear that the interactions between tetravalent actinides and humic substances are very strong and are likely formed through carboxylate groups (Schild and Marquardt, 2000;Geckeis et al, 2002;Reiller et al, 2003;Sachs et al, 2005;Choppin, 2007;Reiller et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation